2019
DOI: 10.1093/geronb/gbz043
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self-Reported Sensory Impairment and Risk of Cognitive Decline and Impairment in the Health and Retirement Study Cohort

Abstract: Objectives We aimed to determine whether self-assessed single (hearing or visual) and dual sensory (hearing and visual) impairments are associated with cognitive decline and incident possible cognitive impairment, no dementia (CIND) and probable dementia. Method Data were drawn from the 1996–2014 surveys of the Health and Retirement Study (HRS), involving 19,618 respondents who had no probable dementia and who were aged 50 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 47 publications
13
103
0
Order By: Relevance
“…Although still limited in number, these studies report consistent results, supporting the hypothesis of an increased risk of dementia which remains significant even after statistically accounting for potential confounders such as demographic and/or cardiovascular factors. Such results have been gathered from studies considering hearing loss either with audiometric measures [15,27,28], speech recognition tests [29], or indirect/self-reported measures [30][31][32]. Although most of the studies considered peripheral hearing loss, the link between age-related central auditory processing disorder [33] and cognitive decline and/or dementia has also been reported by two longitudinal studies [34,35].…”
Section: Hearing Loss and Age-related Cognitive Decline: Two Highly Fmentioning
confidence: 99%
“…Although still limited in number, these studies report consistent results, supporting the hypothesis of an increased risk of dementia which remains significant even after statistically accounting for potential confounders such as demographic and/or cardiovascular factors. Such results have been gathered from studies considering hearing loss either with audiometric measures [15,27,28], speech recognition tests [29], or indirect/self-reported measures [30][31][32]. Although most of the studies considered peripheral hearing loss, the link between age-related central auditory processing disorder [33] and cognitive decline and/or dementia has also been reported by two longitudinal studies [34,35].…”
Section: Hearing Loss and Age-related Cognitive Decline: Two Highly Fmentioning
confidence: 99%
“…6,7 Moreover, a similarly significant association has also been found between cognitive decline and self-reported hearing difficulties in older adults without standardised hearing tests. 8 Routine cognitive screening tools rely on oral administration of instructions and stimuli and implicitly assume normal hearing. Individuals with hearing loss may, however, make frequency-specific phoneme errors that correspond to their audiometric profile, and thus fail elements of the test due to their poor hearing rather than cognitive impairment, potentially leading to false-positive results when screening for potential cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The Sense-Cog WP1 group are Geir Bertelsen 1,2 , Suzanne Cosh 3 , Audrey Cougnard-Grégoire 4 , Piers Dawes 5 , Cécile Delcourt 4 , Fofi Constantinidou 6 , Andre Goedegebure 7 , Catherine Helmer 4 , M. Arfan Ikram 8,9 , Caroline CW Klaver 8,10 , Iracema Leroi 11 , Asri Maharani 11,12 , Magda Meester-Smor 8,10 , Virginie Nael 4 , Neelke Oosterloo 7 ; Neil Pendleton 11,12 , Henrik Schirmer 13 , Gindo Tampubolon 14 , Henning Tiemeier 8,15 , Therese von Hanno 16,17 .…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…There is growing evidence that hearing impairment is independently associated with the magnitude of cognitive decline [4,5] and incident dementia [6][7][8][9]. In an earlier analysis of three nationally representative longitudinal data sets from the United States and Europe, we found that sensory (hearing and/or visual) impairment was associated with accelerated cognitive decline among people aged 50 or older and that the association was stronger among those with dual sensory (hearing and visual) impairment [10].…”
Section: Introductionmentioning
confidence: 99%